2019
DOI: 10.1111/jfpp.14160
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, identification, and activity evaluation of antioxidant peptides from protein hydrolysate of corn germ meal

Abstract: Information on antioxidant peptides derived from corn germ meal (CGM) is seldom reported. In this paper, three novel antioxidant peptides including Met–Gly–Gly–Asn (MGGN; 377.42 Da), Met–Asn–Asn (MNN; 377.42 Da), and Met–Glu–Asn (MEN; 392.43 Da) were purified from the most active fractions of corn germ meal hydrolysate, and their activity was evaluated by radical scavenging, oxygen radical absorbance capacity, cellular antioxidant activity (CAA), and intracellular reactive oxygen species scavenging assays. MNN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Xie et al (2019) reported that different molecular fractions from mung bean protein hydrolysates (MBPHs) exhibited different antioxidant ability and ACE inhibitory activity, where MBPHs-I (<3,000 Da) exhibited the strongest DPPH-and hydroxyl radicals-scavenging activity. Zhang et al (2019) also found that low molecular fractions (<1,000 Da) from protein hydrolysate of corn germ meal showed higher DPPH-and ABTS + radicalsscavenging activity than other fractions (1,000−3,000 Da and 3,000−10,000 Da). Previous reports indicated that low molecular weight fractions from protein hydrolysates exhibited stronger antioxidant ability than high molecular weight protein and hydrolysates (Zheng et al, 2018).…”
Section: Molecular Weight Distribution Of Wjsphsmentioning
confidence: 78%
See 1 more Smart Citation
“…Xie et al (2019) reported that different molecular fractions from mung bean protein hydrolysates (MBPHs) exhibited different antioxidant ability and ACE inhibitory activity, where MBPHs-I (<3,000 Da) exhibited the strongest DPPH-and hydroxyl radicals-scavenging activity. Zhang et al (2019) also found that low molecular fractions (<1,000 Da) from protein hydrolysate of corn germ meal showed higher DPPH-and ABTS + radicalsscavenging activity than other fractions (1,000−3,000 Da and 3,000−10,000 Da). Previous reports indicated that low molecular weight fractions from protein hydrolysates exhibited stronger antioxidant ability than high molecular weight protein and hydrolysates (Zheng et al, 2018).…”
Section: Molecular Weight Distribution Of Wjsphsmentioning
confidence: 78%
“…Zhang et al. (2019) also found that low molecular fractions (<1,000 Da) from protein hydrolysate of corn germ meal showed higher DPPH‐ and ABTS + radicals‐scavenging activity than other fractions (1,000−3,000 Da and 3,000−10,000 Da). Previous reports indicated that low molecular weight fractions from protein hydrolysates exhibited stronger antioxidant ability than high molecular weight protein and hydrolysates (Zheng et al., 2018).…”
Section: Resultsmentioning
confidence: 95%
“…The research of corn active peptides mainly focuses on antioxidant peptides, which have been isolated from corn gluten meal, corn germ, and corn silk. , In contrast, rice active peptides have a wide range of research. Tong found that the rice-derived peptide AAGALPS (25 μg/mL) attenuated TNF-α-induced injury by restraining inflammatory responses and oxidative stress in human umbilical vein endothelial cells .…”
Section: Sourcesmentioning
confidence: 99%
“…Oxidative stress can cause a series of diseases (Chou et al., 2013; Shin et al., 2019; Zhang et al., 2019). Antioxidant ability as one of the main functions of bioactive peptides is widely studied (Hou et al., 2019; Tonolo et al., 2020).…”
Section: Introductionmentioning
confidence: 99%